A utopia do universal em "Paysages Planétaires" de Henri Pousseur - Lucas Filipe Alves de Oliveira (2022)
The electroacoustic piece Paysages Planétaires, from Belgian composer Henry Pousseur, is analyzed as a mean to discuss the presence of non-western elements in contemporary concert music having as its main focus the universalist discourse inherited from XX century aesthetics, primarily derived from the integral serialism. Two important aspects are approached: 1) the problems related to the blending of radically different sources in the same musical language while revisiting the concept of musical material; 2) the social implications involved in the cultural appropriation of external elements by composers from the academic field. For this purpose, Pierre Bourdieu's sociologic theory is mobilized to compare the cultural industry appropriation with that originated from the classic production field.